New Magnetic Anomaly Map of the Antarctic. Issue 13 (6th July 2018) - Golynsky, A. V.; Ferraccioli, F.; Hong, J. K.; Golynsky, D. A.; von Frese, R. R. B.; Young, D. A.; Blankenship, D. D.; Holt, J. W.; Ivanov, S. V.; Kiselev, A. V.; Masolov, V. N.; Eagles, G.; et al.
Abstract: The second generation Antarctic magnetic anomaly compilation for the region south of 60°S includes some 3.5 million line‐km of aeromagnetic and marine magnetic data that more than doubles the initial map's near‐surface database. For the new compilation, the magnetic data sets were corrected for the International Geomagnetic Reference Field, diurnal effects, and high‐frequency errors and leveled, gridded, and stitched together. The new magnetic data further constrain the crustal architecture and geological evolution of the Antarctic Peninsula and the West Antarctic Rift System in West Antarctica, as well as Dronning Maud Land, the Gamburtsev Subglacial Mountains, the Prince Charles Mountains, Princess Elizabeth Land, and Wilkes Land in East Antarctica and the circumjacent oceanic margins. Overall, the magnetic anomaly compilation helps unify disparate regional geologic and geophysical studies by providing new constraints on major tectonic and magmatic processes that affected the Antarctic from Precambrian to Cenozoic times. Plain Language Summary: Given the ubiquitous polar cover of snow, ice, and seawater, the magnetic anomaly compilation offers important constraints on the global tectonic processes and crustal properties of the Antarctic. It also links widely separated areas of outcrop to help unify disparate geologic studies and provides insights on the lithospheric transition between Antarctica and adjacent oceans, as well as the geodynamic evolution of the Antarctic lithosphere in the assembly and breakup of the Gondwana, Rodinia, and Columbia supercontinents and key piercing points for reconstructing linkages between the protocontinents. The magnetic data together with ice‐probing radar and gravity information greatly facilitate understanding the evolution of fundamental large‐scale geological processes such as continental rifting, intraplate mountain building, subduction and terrane accretion processes, and intraplate basin formation. Key Points: We present a new 1.5‐km grid of Antarctic near surface magnetic anomalies The compilation contains more than 3.5 million line‐km of airborne and shipborne data The magnetic anomaly compilation is a new tool to investigate the Antarctic lithosphere and subglacial geology